Scale Using Controls and Criteria in Terms of Position and Orientation During the Analytical Study of Athletes Biomechanical Performance - mohad , ameur; khineche , ali (sports creativity, 2025)
The kinematic analysis is a process that depends on scientific techniques to enhance and develop the level of the athlete performance in order to achieve the goal. This process depends on technological means to facilitate the level of understanding and access to the required skill performance . Among the methods used For the success of this process is photography (camera),which based on the drawing scale, but the mistake or the error made by researchers is in the selected position of the camera which might be wrong . many studies do not take into account the importance of these standards, what leads to wrong -أ.محاد عامر1 –د. خييش علي2 77 املقذمة:هظس الطخخدام الخنىىلىح ُا في الػمل ُت الخدز ٍب ُت لسٍاطُِىا بىصفها وطُلت لخػصٍص وزفؼ مظخىي ألاداء وجدق ُق إهجاشاث حػنع املظخىي الحق ُقي ملؤهالتهم، ولخدق ُق ذلو ال ً أن ًخم اطخخدامها لرلو الهدف بؼهل مىاطب، وبصىزة جدغم جؼى ٍس لفاءاتهم ، ًبُد م فبالىّظس للخقى ُاث الجد ًدة ًُسي أنّها حظخؼ ُؼ خلق طبل حد ًدة ألثر جفاغل ُّت مالخقىُاث القدًمت، في الخدلُل الحسمي. وبمااااا أن امل ُهاه ُهاااااا الح ُى ٍاااات حػمااااال غلااااى دزاطااااات الظااااالىك الحسمااااي فاااااي طااااىء القاااااىاهين واملباااااادا ً خاااالى ً جؼب ُق ُااه غلاااى الجظااام البؼااسي، فمااا الفيز ًاب ُاات الػامااات، أي مداولااات لخؼب ُااق ماااا ًمنااا ً الخىصل إلى خلىى مالبمت لخؼى ٍس ألاد الخدل ُل امل ُهاه ُهي ًمناء الفني. ً أغااساض امل ُهاه ُهااا الح ُى ٍاات وطااؼ اخخبااازاث مىطااىغ ُت لخقاا ُم الحسماااث الس ٍاطاا ُت وذلااو وماا للخػسف غلى أخؼاء ألاداء والدؼاافها إزىااء ألاداء السٍاضا ي ، ما ً خاالى الخدلُال الحسماي ، ٌػاد ً فااسوع غلااام الب ُاااى م ُهاه ُاااو بااال وهااى ألاطااااض الاااري ٌظااادىد غل ُاااه هااارا هاارا ألاخيااار فاااسع مهااام مااا الػلااام ومىاااه ٌظاااخمد بُاهاجاااه الخاااام ... وغلُاااه فاااأن املبااادأ ألاطاكااا ي للمهاااخم باااالبُى مُهاهُاااو هاااى إلاملااام بقىاغاااد الخدلُااال الحسماااي وبػااالع غليهاااا بمااا يء مااا ً الخفصااُل مااا ً احااال مػسفااات مصاااادز املػلىمااااااث ولُفُااااات جسحمااااات و جأوٍااااال ألاخااااادار والىخاااااابج ، باغخمااااااده با طااااااض غلاااااى اطاااااخخدام القاااىاهين وألاطاااع املظاااخخدمت فاااي غلااام البُاااى مُهاهُاااو، هااارا ًاااخم بخجصبااات الفػالُااات السٍاطاااُت ً الىصاااااىى إلاااااي إلادزاك الػامااااال لهااااال ، خصىصاااااا الدزاطااااات التاااااي جخاااااص ً مااااا املدزوطااااات لىاااااخمن الهااااااب ً الواااااي ، والاااااري ال ًمنااااا ً جدقُقااااااه إال ماااااا ً خاااااالى ججمُاااااؼ ألاحاااااصاء والػىاصاااااس فاااااي وخااااادة مخهاملت . وغلُاه فالخدلُال فاي املجااىً الػلاىم املهمات التاي حػخمااد غلاى غلاىم أخاسي مالدؼااس ٍذ الس ٍاضاا ي ما وامل ُهاه ُها الح ُى ٍت والفيز ًاء والس ٍاط ُاث والػلاىم ألاخاسي املسجبؼات بالحسلات , إن الخدل ُال أداة results and reflecte the study, and to clarify this, we have done this analytical study to determine the controls that are taken into account in the use of this tool to come up with real values that reflect the level of evaluation where the analytical approach was followed . The sample was composed of school athletes in Djelfa. We used drawing scale tools, a photographic camera and analysis programs. The conclusion of the work was that most of these studies are defective during photography what led to wrong judgment on the studied performance.